Organoleptic Observations of the Preservation of Mackerel Fish using Liquid Smoke from Coconut Shells Pyrolysis - Aladin, Andi; Yani, Setyawati; Syarif, Takdir; Modding, Basri; Wiyani, Lastri (World Chemical Engineering Journal, 2022)
Liquid smoke is a by-product of a pyrolysis process of coconut shells to produce coconut shell charcoal. The liquid can be used as an alternative fish preservative. Traditionally, the fish preservation is conducted by direct smoking of the fish on a coal or biomass burning. However, due to the presence of benzopyrene compounds in the direct smoking process, the smoked fish produced may pose a health risk as benzopyrine is carcinogenic. In this research, a free benzopyrene liquid smoke obtained from the pyrolysis of coconut shells which is called grade 1 liquid smoke  is used for mackerel fish preservative. The aim of this research is to evaluate the effect of soaking time to the quality of preserved mackarel fish using organoleptic approaches. Five (5) pair of fresh mackerel fishes were cleaned and placed in a  soaking container. There was also one (1) pair of mackerel used as a control. Approximately  3L of 3% (wt.) solution of liquid smoke from coconut shell pyrolysis was poured into the soaking container  until the fishes were perfectly soaked. The fishes were soaked for 3, 5, 10, 15 and 20 minutes, respectively, and then they were stored at room temperature for observation. The control fish was stored in a container in room temperature without the addition of liquid smoke . Organoleptic observations, namely aroma, color and texture were carried out for soaked and control fishes in the first and 48th  hours of the storage time. From the research, it was found that the optimum soaking time of mackerel fishes was 5 minutes. At this optimum soaking time, the organoleptic properties including aroma, color and texture  of preserved fishes  at the first hour of the storage showed only one level  lower quality than a fresh fish. Furthermore, at 48th hours of the storage time, the preserved fishes showed a better performance of organoleptic characteristics (scale >4 ) compared to the control fish (scale @2).